2015
DOI: 10.1002/2015jc011173
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term variations in global sea level extremes

Abstract: Decadal to multidecadal variations in sea level extremes unrelated to mean sea level changes have been investigated using long tide gauge records distributed worldwide. A state space approach has been applied that provides robust solutions and uncertainties of the time evolving characteristics of extremes, allowing for data gaps and uneven sampling, both common features of historical sea level time series. Two different models have been formulated for the intensity and for the occurrence of extreme sea level e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(126 citation statements)
references
References 46 publications
5
120
1
Order By: Relevance
“…However, despite strong correlations between some regions around the North American coastline and across the Atlantic to the North Sea, none of the correlations are significant at the 95% level. Just prior to completing our study, we learnt of a similar investigation by Marcos et al (2015). Using the GESLA dataset, they showed that the intensity and frequency of ESL unrelated to MSL display a regional coherence on decadal time-scales.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…However, despite strong correlations between some regions around the North American coastline and across the Atlantic to the North Sea, none of the correlations are significant at the 95% level. Just prior to completing our study, we learnt of a similar investigation by Marcos et al (2015). Using the GESLA dataset, they showed that the intensity and frequency of ESL unrelated to MSL display a regional coherence on decadal time-scales.…”
Section: Discussionmentioning
confidence: 72%
“…Using the GESLA dataset, they showed that the intensity and frequency of ESL unrelated to MSL display a regional coherence on decadal time-scales. Their finding points toward large-scale climate drivers of decadal changes in storminess (Marcos et al, 2015). The string correlations between neighboring sites show that these large scale climatic drivers are important, but there significance is difficult to assess in relatively short datasets have a high degree of temporal autocorrelation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most areas of the world, secular changes in extreme WLs over the last century have been found to be of similar magnitude as the rise in MSL (see e.g., Woodworth and Blackman, 2004;Menéndez and Woodworth, 2010). In recent years some studies have additionally identified significant secular trends in both tide and surge components in many regions of the world (Marcos et al, 2015;Mawdsley et al, 2015, for global analyses). However, a better understanding of the links between atmospheric dynamics and extreme WLs variability is needed in order to better model their occurrence probability (see e.g., Cid et al, 2015).…”
Section: Introductionmentioning
confidence: 98%